(untitled) (Journal of Engineering, 2006)
A study has been done to analyze the total production system by developing a computer model. Every component of the production system has been programmed individually and then linked in the composite production system computer program. These components are; reservoir component, vertical component, surface choke component and finally horizontal component. Each of the previous components are developed using various equations or models to determine the pressure loss thorough that component. In the current study the Wiggins method has been used to calculate the IPR curves. The vertical and horizontal components are developed using the unified mechanistic model of Gomez. Lage mechanistic model has been used to calculate the pressure losses through annulus. Perkins mechanistic model is used to calculate the pressure loss through surface chokes. A filed example problem is presented to analyze the production system. This example has been used to determine the optimum system design which maximizes production rate for a set of condition.